Semantic Language Skills in 2-Year-Old Children: A Case Study of Universal Substantive Acquisition at Kampung Baru - Suryanti; Jefriyanto Saud; Azhariah Rachman; Muta'allim; Amiruddin (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
Language acquisition in early childhood is a crucial foundation in individual development as it is a critical period in which children rapidly and naturally learn language and communication. Speaking is a crucial language skill in everyday life. The act of speaking is closely related to language usage, and one example of this is the development of language abilities in 2-year-old children. This study aims to explore the semantic language acquisition in 2-year-old children at Kampung Baru. It is a qualitative descriptive study that focuses on the semantic language of nouns, verbs, and adjectives. This research is presented as an alternative strategy to enhance the intellectual development of children, especially at Kampung Baru, in their understanding of more complex language and communication in the future. The data source is the language used and the gestures by 2-year-old children at Kampung Baru. The data collection method employed in this study is participant observation with a semi-structured interview and complemented by recording, note-taking, and interviews. The researcher observed and recorded conversations of 2-year-old children and noted words related to the research objectives. Additionally, interviews were conducted with families of 2-year-old children at Kampung Baru during two months, specifically regarding nouns, verbs, and adjectives. The research findings indicate that 2-year-old children at Kampung Baru are capable of expressing and acquiring words accurately and in line with their intentions. They can differentiate between spoken words and actions. Furthermore, they demonstrate nonverbal language skills by expressing objects through gestures when referring to nouns, indicating actions when referring to verbs, and displaying attitudes and facial expressions when referring to adjectives.